Electro-peroxone pretreatment for enhanced simulated hospital wastewater treatment and antibiotic resistance genes reduction. (June 2018) - Zheng, He-Shan; Guo, Wan-Qian; Wu, Qu-Li; Ren, Nan-Qi; Chang, Jo-Shu
Abstract: Hospital wastewater is one of the possible sources responsible for antibiotic resistant bacteria spread into the environment. This study proposed a promising strategy, electro-peroxone (E-peroxone) pretreatment followed by a sequencing batch reactor (SBR) for simulated hospital wastewater treatment, aiming to enhance the wastewater treatment performance and to reduce antibiotic resistance genes production simultaneously. The highest chemical oxygen demand (COD) and total organic carbon (TOC) removal efficiency of 94.3% and 92.8% were obtained using the E-peroxone-SBR process. The microbial community analysis through high-throughput sequencing showed that E-peroxone pretreatment could guarantee microbial richness and diversity in SBR, as well as reduce the microbial inhibitions caused by antibiotic and raise the amount of nitrification and denitrification genera. Specially, quantitative real-time PCRs revealed that E-peroxone pretreatment could largely reduce the numbers and contents of antibiotic resistance genes (ARGs) production in the following biological treatment unit. It was indicated that E-peroxone-SBR process may provide an effective way for hospital wastewater treatment and possible ARGs reduction. Graphical abstract: Unlabelled Image Highlights: A combined method of electro-peroxone-SBR was designed for hospital wastewater treatment. Electro-peroxone-SBR had high COD and TOC removal rates even under high concentration of antibiotic residue. E-peroxone pretreatment could raise microbial richness and the abundance of functional bacteria in SBR. ARGs production could be effectively inhibited in this combined treatment system.